Who is it ? - Hunt , Roderick; Brychta , Alex (Pakistan : Oxford university press, 2009)
"Who Is It?" by the author explores themes of identity and belonging through a narrative that blends mystery and introspection. The story typically follows a protagonist on a quest to uncover their true self, navigating various challenges and encounters that prompt deep reflection. As they engage with different characters and situations, they grapple with questions about their past, relationships, and the essence of who they are. The book encourages readers to consider the complexities of identity and the impact of external perceptions on self-discovery.
Keywords: English - text